Functionalized graphene modified polyurethane composite coating and preparation method thereof
By introducing functionalized graphene into polyurethane coatings to form a dense film-like structure, the problems of poor corrosion resistance and low mechanical properties of polyurethane coatings are solved, and higher corrosion resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411795663.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyurethane coatings are prone to degradation when exposed to corrosive electrolytes, resulting in reduced coating adhesion strength and intensified metal corrosion reactions, and low anti-corrosion efficiency of the prior art.
By introducing functionalized graphene into the coating, the two-dimensional sheet structure and high electron density of graphene are used to form a dense film structure, increasing the corrosion resistance and mechanical properties of the coating. The specific steps include esterification of carboxylated graphene with epoxy propyl alcohol to form epoxy graphene, then opening the ring with polyvinyl chloride, grafting the graphene, and reacting with graphene through pyridine groups to form pyridine poly Vinyl chloride grafts graphene and finally blends with polyurethane to prepare the coating.
It improves the corrosion resistance and mechanical properties of polyurethane coatings, enhances the density and stability of the coating, reduces the corrosion rate of metals, and improves the stability and corrosion efficiency of the coatings.
Smart Images

Figure CN119432215A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a functionalized graphene-modified polyurethane composite coating and a preparation method thereof. Background Art
[0002] The serious waste and huge economic losses caused by metal corrosion have attracted widespread attention from the society and have become a problem of global significance. Anti-corrosion coatings have been proven to be one of the most important methods and are often used to protect metals from corrosion. Organic polymer coatings including polyurethane, acrylic resin, epoxy resin, alkyd resin, etc. are widely used as metal anti-corrosion coatings. In terms of the quality of the surface coating, polyurethane coatings are regarded by many as the most economical and reliable choice. However, since polyurethane coatings are exposed to corrosive electrolytes for a long time, the coatings will degrade. The penetration of these ions into the metal will reduce the adhesion strength of the coatings and induce corrosion reactions of the metals under the coatings. Therefore, researchers have introduced different methods to improve the anti-corrosion properties of these polymer coatings. Among them, the patent with Chinese patent publication number CN106947380B discloses an environmentally friendly flame-retardant anti-corrosion coating based on polyurethane, and the patent with Chinese patent publication number CN104293158A discloses a method for preparing fluorine-containing polyurethane coatings and fluorine-containing polyurethane anti-corrosion coatings. Although both increase the anti-corrosion ability of polyurethane coatings by adding anti-corrosion elements, they still have the problem of low anti-corrosion efficiency.
[0003] By adding fillers / additives / pigments to coatings, they effectively enhance the protective properties of polymers. These materials provide a uniform and continuous coating that prevents structural cracking and fractures during stress, physical aging, and water permeability. Recently, nanoparticle-based fillers and additives have attracted much attention due to their large surface area. They provide better protective properties compared to traditional micron-sized additives. In this regard, carbon-based nanomaterials such as graphene, carbon nanotubes, and fullerenes have received much attention. Graphene is composed of sp 2 The two-dimensional (2D) single-atom structure composed of hybrid carbon atoms and cell lattices has a high electron density in its aromatic rings. The dense delocalized two-dimensional electronic state of graphene enables it to shield atoms and molecules, making graphene a candidate material for anti-corrosion applications. When the corrosive medium penetrates the organic coating system, it will bypass or penetrate the filler in the coating, and the tortuosity of the corrosive medium through the coating increases the difficulty of the corrosive medium. In addition, anti-corrosion small molecules such as pyridine and its derivatives are also important substances for increasing the anti-corrosion ability of coatings. Grafting them with inorganic substances can not only increase the anti-corrosion ability of the coating, but also prevent the precipitation of anti-corrosion small molecules and cause the poor stability of the anti-corrosion coating. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a functionalized graphene-modified polyurethane composite coating and a preparation method thereof, which solves the problems of poor corrosion resistance and low mechanical properties of polyurethane coatings.
[0005] To achieve the above object, the present invention provides the following technical solution: a functionalized graphene-modified polyurethane composite coating, wherein the preparation method of the functionalized graphene-modified polyurethane composite coating comprises the following steps: (1) placing carboxylated graphene, glycidol, dicyclohexylcarbodiimide (DCC) and N,N-dimethylaminopyridine (DMAP) in deionized water, stirring evenly, and reacting to obtain epoxidized graphene after the reaction is completed; (2) After polyvinyl chloride, sodium bisulfite and barium zinc stabilizer are uniformly mixed, epoxy graphene is added at 80-120° C., and the mixture is transferred to a double-roll mill for reaction to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, sodium hydride and 2-(methylamino)pyridine are dissolved in tetrahydrofuran solvent, and then polyvinyl chloride grafted graphene is added, stirred evenly, and reacted. After the reaction is completed, pyridine-based polyvinyl chloride grafted graphene is obtained; (4) After the filler pyridine polyvinyl chloride grafted graphene, the dispersant sodium hexametaphosphate and the thickener propylene glycol butyl ether are mixed evenly, the defoaming agent polyether modified silicone, the film-forming aid sorbitan trioleate, the leveling agent hydroxypropyl methylcellulose, deionized water and polyurethane are added and stirred until uniform, thereby obtaining a functionalized graphene modified polyurethane composite coating.
[0006] Preferably, in step (1), the mass ratio of carboxylated graphene, glycidol, dicyclohexylcarbodiimide, N,N-dimethylaminopyridine and deionized water is 100:40-100:80-220:10-35:3500-8000.
[0007] Preferably, in step (1), the reaction temperature is 20-40° C. and the reaction time is 18-36 h.
[0008] Preferably, in step (2), the mass ratio of polyvinyl chloride, sodium bisulfite, barium zinc stabilizer and epoxide graphene is 120-200:20-40:2-6:100.
[0009] Preferably, in step (2), the reaction temperature is 160-200° C., the reaction pressure is 8-12 MPa, and the reaction time is 10-30 min.
[0010] Preferably, in step (3), the mass ratio of sodium hydride, 2-(methylamino)pyridine, tetrahydrofuran, methyl iodide and polyvinyl chloride grafted graphene is 30-60:3-8:2000-5000:100.
[0011] Preferably, in step (3), the reaction temperature is 20-40° C. and the reaction time is 12-24 h.
[0012] Preferably, in step (4), the mass ratio of pyridyl polyvinyl chloride grafted graphene, sodium hexametaphosphate, propylene glycol butyl ether, polyether modified silicone, sorbitan trioleate, hydroxypropyl methylcellulose, deionized water and polyurethane is 1.5-4:3-8:2-5:1-2:2-6:1-4:20-35:100.
[0013] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The functionalized graphene modified polyurethane composite coating comprises the following steps: firstly, in a catalyst system of dicyclohexylcarbodiimide and N,N-dimethylaminopyridine, the carboxyl group of carboxylated graphene is subjected to an esterification reaction with the hydroxyl group of glycidol to obtain epoxidized graphene; then, under the action of a barium zinc stabilizer and with sodium bisulfite as a catalyst, a ring-opening reaction is carried out with a part of chlorine atoms in polyvinyl chloride in a double-roll mill to obtain polyvinyl chloride grafted graphene; then, with sodium hydride as a reducing agent, the imine group of 2-(methylamino)pyridine is subjected to a reaction with the chlorine atoms of the graphene grafted polyvinyl chloride to obtain pyridine-based polyvinyl chloride grafted graphene; and finally, the functionalized graphene modified polyurethane composite coating is prepared by ultrasonic blending.
[0014] Compared with the maze-like shielding structure of traditional polyurethane coatings, the functionalized graphene-modified polyurethane composite coating has a polyurethane coating with added functionalized graphene. Through the layered superposition of the two-dimensional flake structure of graphene, a denser film structure can be formed, thereby increasing the corrosion resistance and mechanical properties of the polyurethane coating. Due to the nanometer size of graphene and the high surface hydrophobicity, the graphene is filled in the tiny holes in the coating, which can not only reduce the pore structure of the coating by layered superposition to form a denser physical isolation layer, but also prevent water molecules from entering the coating protective layer through the remaining pores and contacting the metal surface due to the strong hydrophobicity, thereby reducing the corrosion rate of the metal. In addition, graphene itself has extremely strong conductivity and can act as a conductor in the coating, so that the electrons of the metal in the anode reaction are transferred to the coating surface, reducing the accumulation of metal ions and further slowing down the electrochemical corrosion rate of the metal. In addition, the high mechanical properties of graphene itself also improve the mechanical properties of the coating. When graphene exists in polyurethane coatings, it can form a highly cross-linked network structure with polyurethane. With the help of the network structure, when polyurethane is subjected to external force, the external stress is dispersed inside the polyurethane coating, reducing the degree of damage to the polyurethane film and increasing its mechanical properties. In addition, aminopyridine is an excellent corrosion inhibitor that can react with the metal rust layer and generate a denser membrane structure, reduce the pore structure of the membrane, improve the corrosion current and impedance value of the polyurethane coating, and enhance its anti-corrosion performance. Grafting aminopyridine on the surface of graphene not only increases the synergistic effect between the two, further enhances the anti-corrosion effect between the two, but also improves the dispersion of graphene in the matrix, avoids the precipitation of aminopyridine small molecules during use, and increases the stability of the anti-corrosion coating. Moreover, through the preparation method of blending, the chain segments of polyvinyl chloride and the flexible chain segments of polyurethane are compatible, so that the hard segments in the polyurethane coating are increased and the separation zone is expanded, further increasing the mechanical properties of the polyurethane coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the reaction formula of polyvinyl chloride and graphene oxide; Figure 2 It is the reaction formula of 2-(methylamino)pyridine and polyvinyl chloride grafted graphene. DETAILED DESCRIPTION
[0016] To achieve the above object, the present invention provides the following specific implementation methods and examples: A functionalized graphene-modified polyurethane composite coating, the preparation method of which comprises the following steps: (1) placing carboxylated graphene, glycidol, dicyclohexylcarbodiimide (DCC) and N,N-dimethylaminopyridine (DMAP) in deionized water at a mass ratio of 100:40-100:80-220:10-35:3500-8000, stirring evenly, reacting at 20-40°C for 18-36h, filtering after the reaction, and washing with deionized water to obtain epoxidized graphene; (2) Mix polyvinyl chloride, sodium bisulfite and barium zinc stabilizer in a mass ratio of 120-200:20-40:2-6:100, then add epoxidized graphene at 80-120° C., transfer to a double-roll mill, and react at a temperature of 160-200° C. and a pressure of 8-12 MPa for 10-30 min to obtain polyvinyl chloride grafted graphene; (3) Dissolving sodium hydride and 2-(methylamino)pyridine in tetrahydrofuran solvent at a mass ratio of 30-60:3-8:2000-5000:100 under a nitrogen atmosphere, adding polyvinyl chloride grafted graphene, stirring evenly, reacting at 20-40° C. for 12-24 hours, filtering after the reaction, washing with ethanol and deionized water to obtain pyridine-based polyvinyl chloride grafted graphene; (4) After the filler pyridine polyvinyl chloride grafted graphene, the dispersant sodium hexametaphosphate and the thickener propylene glycol butyl ether are mixed evenly in a mass ratio of 1.5-4:3-8:2-5:1-2:2-6:1-4:20-35:100, the defoaming agent polyether modified silicone, the film-forming aid sorbitan trioleate, the leveling agent hydroxypropyl methylcellulose, deionized water and polyurethane are added and stirred until uniform, thereby obtaining a functionalized graphene modified polyurethane composite coating. Example 1
[0017] (1) Place 5 g of carboxylated graphene, 2 g of propylene oxide, 4 g of dicyclohexylcarbodiimide (DCC) and 0.5 g of N,N-dimethylaminopyridine (DMAP) in 175 mL of deionized water, stir evenly, and react at 20 °C for 18 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) 6 g of polyvinyl chloride, 1 g of sodium bisulfite, and 0.1 g of barium zinc stabilizer were mixed evenly, and then 5 g of epoxidized graphene was added at 80 ° C. The mixture was transferred to a double-roll mill and reacted at a temperature of 160 ° C. and a pressure of 8 MPa for 10 min to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, 1.2 g of sodium hydride and 0.12 g of 2-(methylamino)pyridine were dissolved in 80 g of tetrahydrofuran solvent, and 4 g of polyvinyl chloride grafted graphene was added. After stirring evenly, the mixture was reacted at 20 °C for 12 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain pyridine-based polyvinyl chloride grafted graphene. (4) After 0.15 g of filler pyridine polyvinyl chloride grafted graphene, 0.3 g of dispersant sodium hexametaphosphate and 0.2 g of thickener propylene glycol butyl ether are mixed evenly, 0.1 g of defoaming agent polyether modified silicone, 0.2 g of film-forming aid dehydrated sorbitan trioleate, 0.1 g of leveling agent hydroxypropyl methylcellulose, 2 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a functionalized graphene modified polyurethane composite coating. Example 2
[0018] (1) Place 5 g of carboxylated graphene, 3 g of propylene oxide, 5 g of dicyclohexylcarbodiimide (DCC) and 0.8 g of N,N-dimethylaminopyridine (DMAP) in 200 mL of deionized water, stir evenly, and react at 25 °C for 24 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) 7 g of polyvinyl chloride, 1.2 g of sodium bisulfite, and 0.15 g of barium zinc stabilizer were mixed evenly, and then 5 g of epoxidized graphene was added at 90 ° C. The mixture was transferred to a double-roll mill and reacted at a temperature of 170 ° C. and a pressure of 9 MPa for 14 min to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, 1.6 g of sodium hydride and 0.18 g of 2-(methylamino)pyridine were dissolved in 100 g of tetrahydrofuran solvent, and 4 g of polyvinyl chloride grafted graphene was added. After stirring evenly, the mixture was reacted at 25 °C for 18 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain pyridine-based polyvinyl chloride grafted graphene. (4) After 0.2 g of filler pyridine polyvinyl chloride grafted graphene, 0.4 g of dispersant sodium hexametaphosphate and 0.3 g of thickener propylene glycol butyl ether are mixed evenly, 0.12 g of defoaming agent polyether modified silicone, 0.3 g of film-forming aid dehydrated sorbitan trioleate, 0.2 g of leveling agent hydroxypropyl methylcellulose, 2.5 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a functionalized graphene modified polyurethane composite coating. Example 3
[0019] (1) Place 5 g of carboxylated graphene, 4 g of propylene oxide, 8 g of dicyclohexylcarbodiimide (DCC) and 1.5 g of N,N-dimethylaminopyridine (DMAP) in 300 mL of deionized water, stir evenly, and react at 30 ° C for 32 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) 8 g of polyvinyl chloride, 1.6 g of sodium bisulfite, and 0.24 g of barium zinc stabilizer were mixed evenly, and then 5 g of epoxidized graphene was added at 110°C, transferred to a double-roll mill, and reacted at a temperature of 190°C and a pressure of 11 MPa for 25 min to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, 2 g of sodium hydride and 0.26 g of 2-(methylamino)pyridine were dissolved in 160 g of tetrahydrofuran solvent, and 4 g of polyvinyl chloride grafted graphene was added. After stirring evenly, the mixture was reacted at 35 °C for 20 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain pyridine-based polyvinyl chloride grafted graphene. (4) After 0.35 g of filler pyridine polyvinyl chloride grafted graphene, 0.6 g of dispersant sodium hexametaphosphate and 0.4 g of thickener propylene glycol butyl ether are mixed evenly, 0.16 g of defoaming agent polyether modified silicone, 0.5 g of film-forming aid dehydrated sorbitan trioleate, 0.3 g of leveling agent hydroxypropyl methylcellulose, 3 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a functionalized graphene modified polyurethane composite coating. Example 4
[0020] (1) Place 5 g of carboxylated graphene, 5 g of propylene oxide, 11 g of dicyclohexylcarbodiimide (DCC) and 1.75 g of N,N-dimethylaminopyridine (DMAP) in 400 mL of deionized water, stir evenly, and react at 40 °C for 36 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) 10 g of polyvinyl chloride, 2 g of sodium bisulfite, and 0.3 g of barium zinc stabilizer were mixed evenly, and then 5 g of epoxidized graphene was added at 120 ° C. The mixture was transferred to a double-roll mill and reacted at a temperature of 200 ° C. and a pressure of 12 MPa for 30 min to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, 2.4 g of sodium hydride and 0.32 g of 2-(methylamino)pyridine were dissolved in 200 g of tetrahydrofuran solvent, and 4 g of polyvinyl chloride grafted graphene was added. After stirring evenly, the mixture was reacted at 40 °C for 24 h. After the reaction was completed, the mixture was filtered and washed with ethanol and deionized water to obtain pyridine-based polyvinyl chloride grafted graphene. (4) After 0.4 g of filler pyridine polyvinyl chloride grafted graphene, 0.8 g of dispersant sodium hexametaphosphate and 0.5 g of thickener propylene glycol butyl ether are mixed evenly, 0.2 g of defoaming agent polyether modified silicone, 0.6 g of film-forming aid dehydrated sorbitan trioleate, 0.4 g of leveling agent hydroxypropyl methylcellulose, 3.5 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a functionalized graphene modified polyurethane composite coating.
[0021] Comparative Example 1 (1) Place 5 g of carboxylated graphene, 3 g of propylene oxide, 8 g of dicyclohexylcarbodiimide (DCC) and 0.9 g of N,N-dimethylaminopyridine (DMAP) in 300 mL of deionized water, stir evenly, and react at 30 °C for 24 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) 8 g of polyvinyl chloride, 1 g of sodium bisulfite, and 0.2 g of barium zinc stabilizer were mixed evenly, and then 5 g of epoxidized graphene was added at 90 ° C. The mixture was transferred to a double-roll mill and reacted at a temperature of 180 ° C. and a pressure of 9 MPa for 15 min to obtain polyvinyl chloride grafted graphene; (3) After 0.3 g of filler polyvinyl chloride grafted graphene, 0.7 g of dispersant sodium hexametaphosphate and 0.4 g of thickener propylene glycol butyl ether are mixed evenly, 0.12 g of defoaming agent polyether modified silicone, 0.3 g of film-forming aid dehydrated sorbitan trioleate, 0.2 g of leveling agent hydroxypropyl methylcellulose, 2.5 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a functionalized graphene modified polyurethane composite coating.
[0022] Comparative Example 2 (1) Place 5 g of carboxylated graphene, 4 g of propylene oxide, 9 g of dicyclohexylcarbodiimide (DCC) and 1 g of N,N-dimethylaminopyridine (DMAP) in 200 mL of deionized water, stir evenly, and react at 30 °C for 24 h. After the reaction is completed, filter and wash with deionized water to obtain epoxidized graphene; (2) After 0.2 g of filler graphene, 0.5 g of dispersant sodium hexametaphosphate and 0.3 g of thickener propylene glycol butyl ether are mixed evenly, 0.14 g of defoaming agent polyether modified silicone, 0.3 g of film-forming aid dehydrated sorbitan trioleate, 0.3 g of leveling agent hydroxypropyl methylcellulose, 3.5 g of deionized water and 10 g of polyurethane are added and stirred until uniform to obtain a graphene-modified polyurethane composite coating.
[0023] The anti-corrosion test of functionalized graphene modified polyurethane composite coating was carried out in accordance with the national standard GB / T 30790.1-2014.
[0024]
[0025] The mechanical properties of functionalized graphene modified polyurethane composite coatings were tested in accordance with the national standard GB / T 19250-2013.
[0026]
Claims
1. A functionalized graphene-modified polyurethane composite coating, characterized in that: The preparation method of the functionalized graphene-modified polyurethane composite coating comprises the following steps: (1) placing carboxylated graphene, glycidol, dicyclohexylcarbodiimide (DCC) and N,N-dimethylaminopyridine (DMAP) in deionized water, stirring evenly, and reacting to obtain epoxidized graphene after the reaction is completed; (2) After polyvinyl chloride, sodium bisulfite and barium zinc stabilizer are uniformly mixed, epoxy graphene is added at 80-120° C., and the mixture is transferred to a double-roll mill for reaction to obtain polyvinyl chloride grafted graphene; (3) Under a nitrogen atmosphere, sodium hydride and 2-(methylamino)pyridine are dissolved in tetrahydrofuran solvent, and then polyvinyl chloride grafted graphene is added, stirred evenly, and reacted. After the reaction is completed, pyridine-based polyvinyl chloride grafted graphene is obtained; (4) After the filler pyridine polyvinyl chloride grafted graphene, the dispersant sodium hexametaphosphate and the thickener propylene glycol butyl ether are mixed evenly, the defoaming agent polyether modified silicone, the film-forming aid sorbitan trioleate, the leveling agent hydroxypropyl methylcellulose, deionized water and polyurethane are added and stirred until uniform, thereby obtaining a functionalized graphene modified polyurethane composite coating.
2. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (1), the mass ratio of carboxylated graphene, glycidol, dicyclohexylcarbodiimide, N,N-dimethylaminopyridine and deionized water is 100:40-100:80-220:10-35:3500-8000.
3. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (1), the reaction temperature is 20-40° C. and the reaction time is 18-36 hours.
4. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (2), the mass ratio of polyvinyl chloride, sodium bisulfite, barium zinc stabilizer and epoxide graphene is 120-200:20-40:2-6:
100.
5. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (2), the reaction temperature is 160-200° C., the reaction pressure is 8-12 MPa, and the reaction time is 10-30 min.
6. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (3), the mass ratio of sodium hydride, 2-(methylamino)pyridine, tetrahydrofuran, methyl iodide and polyvinyl chloride grafted graphene is 30-60:3-8:2000-5000:
100.
7. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (3), the reaction temperature is 20-40° C. and the reaction time is 12-24 h.
8. The functionalized graphene-modified polyurethane composite coating according to claim 1, characterized in that: In the step (4), the mass ratio of pyridyl polyvinyl chloride grafted graphene, sodium hexametaphosphate, propylene glycol butyl ether, polyether modified silicone, sorbitan trioleate, hydroxypropyl methylcellulose, deionized water and polyurethane is 1.5-4:3-8:2-5:1-2:2-6:1-4:20-35:100.
Citation Information
Patent Citations
Method of preparing fluorinated polyurethane paint and fluorinated polyurethane anticorrosive paint
CN104293158A
An environmentally friendly flame-retardant and anti-corrosion coating based on polyurethane
CN106947380B
Cited By
Long-acting anti-corrosion polyvinyl chloride fluorine-containing minium coating as well as preparation method and application thereof
CN121086599A